(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
The present study was undertaken to find out the prevalence of gastrointestinal nematodes in pigeon (columba livia) at Rajshahi division from 01-01-2016 to 15-12-2016 and to evaluate the comparative efficacy piparazine citrate and levamisole HCL. Total 3 different species of parasites were recorded in this study and those were Ascaridia columbae, Capillilaria obsignata, Raillietina tetragona. Out of 263 pigeon, 109 pigeon having ascarid and capillaria positive were treatment with piparazine citrate and levamisole HCL. The pigeon were treated with recommended (10g mixed in 6 litre drinking water for 100 pigeon) dose of Ascarex® and recommended (1gm mixed in 1 litre drinking water) dose of Avinex® orally, respectively. The recovery rate of ascariasis at 7th days was 50.9% and capillariasis was 51.85%. After 21th days the recovery rate of ascariasis was 72.72% and capillariasis was 66.66%. The efficacy of drugs is more in case of young (77.27% at 7th days and 87.36% at 21th days) than adult (44.82% at 7th days and 65.51% at 21th days).In exotic breeds efficacy is good (60.41% at 7th days and 85.41% at 21th days) than indigenous breeds (44.26% at 7th days and 66.65% at 21th days). The recovery rate is more in traditional (65.3% at 7th days and 78.33% at 21th days) than commercial farming system (42.85% at 7th days and 58.33% at 21th days). Res. Agric., Livest. Fish.6(2): 323-328, August 2019